Pengaruh Pengembangan Pariwisata Pedesaan Terhadap Penurunan Kemiskinan Dalam Perspektif SDGS 1 Dengan Dukungan Kelembagaan Sebagai Variabel Moderasi: Pendekatan SEM - Muhammad Arif Febrian; Amrullah; Muh. Fahrurrozi (Penerbit Lafadz Jaya, 2026)
Write a brief summary of your research, including objectives, methods, results, and conclusions. Limit to 250 words This study aims to analyze the impact of rural tourism development on poverty reduction in Loyok Tourism Village, with institutional support as a moderating variable. Using a quantitative approach, this research applies Structural Equation Modeling (SEM-PLS) to 379 respondents to examine causality and the mediating roles of community empowerment and income. The results indicate that tourism development has a positive and significant effect on community empowerment (t=14.685; p=0.000) and community income (t=14.243; p=0.000). Furthermore, empowerment (t=2.189; p=0.029) and community income (t=4.109; p=0.000) contribute significantly to poverty reduction. However, the analysis reveals that the mediating variables do not significantly mediate the effect, and institutional support fails to moderate the relationship between tourism development and poverty reduction (p=0.175). These findings suggest that the economic benefits of tourism are not yet inclusively distributed and that local-level institutional roles are not yet optimal in supporting the SDG 1 target.